Odzsnioscopie analysis of human remains from crematory burials - Kaczmarek, Maria (Anthropological Review, 1981)
In order to stale possibility of edontoscopie examinations of human remains frem crematory burials, morphelogieal structures of permanent teoth crown germs have been observed in children aged 6-14 from 139 graves of Pommeranian Culture (V-IIc. B.C) excavated at various (226) archeological sites. Traditionaly examined odontological crown structures have been observed: shovel-shaped form of maxillary incisors, occlusal patterns of premolars, muxillary molars (hypocone reduction) and mandibular ones (cusp reduction and type of furrows separuting them), eventualiy, tuberculum Carabelii on first maxillary molar. Lack of attrition en veclusal surface enables particular observations of odontoglyphie elements such as 1pa on the first maxillary molar, endings of 2med on the first mandibular molar and type of lend and 2end furrows on the second mundibular molar. From observations of all previously mentioned struciures it may be seen that morphological characteristics of remains from cremutory burials may be widened to odortsscopic description of tooth crowns as well as to odontoglyphics for permanent tooth cova germs are preserved in an almost intact state. The results obtained for frequencies of examined crown elements are very similar to Polish and European skeletal populations from various historical periods except for tuberculum Carabelli cad mandibular molars reduction. These dental traits demostrate specific adaptive s in the dentition of described group.